(3efXhQ JWHjbjs - (3aGjR LeYg(B, (3GdfLGQs; (3fHjd LeYg(B, (3GdfLGQs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2009)
(3eaghe GdHMK GdYdej hWQb GdhUhd Gdi GdeYQaI eY JfGhd UjGZI JUeje GdHMK hGfhGYg hcPG WQb h GOhGJ LeY GdHjGfGJ h GNJjGQ GdYjfI hGfhGYgG h TQhW GSJYeGdgG eY GdJWQb GdiGdeJZjQGJ hGdebGjjS hcPdc eaGgje GMUGFjI hcPG JMdjd GdHjGfGJ hGNJHGQ GdaQVjGJ hYQVgG eY JHjGf GgejI GdJhKjb aj GdHMK GdYdejs
(3eQGLY U(B.299 (3; edGMb U(B.305s
Keywords: (3CSGdjH GdHMKs; (3GdHMK GdYdejs; (3GdHMhKs; (3WQb GdHMKs